Teachers knowledge on dental and mouth health at primary school - Fajri, Raiandri; Suwargiani, Anne Agustina; Suryanti, Netty (Universitas Padjadjaran, 2013)
Introduction: Oral and dental health problems in elementary school-age children are problems that require treatment, both preventive and promotive. Government efforts in improving dental health knowledge of elementary school-age children are made through business Dental School Health (UKGS) by involving teachers. The teacher has the role of delivering knowledge of the causes and prevention of dental and oral health in children. Purpose of the research is to find out teacher’s knowledge about oral health. Methods: The method used is descriptive, using survey techniques. Research population include 28 teachers. The study sample was all members of the population in the Public Elemen-tary School (total sampling). Results: The results showed that the teacher’s knowledge about dental disease and the mouth and oral hygiene are categorized as good; knowledge about the anatomy of the oral cavity, various teeth and how to brush teeth properly are categorized as fairly good, and tooth growth knowledge and dental anatomy are cat-egorized as bad. Conclusion: The teacher does not understand oral health. Knowledge level of the teachers will influ-ence the implementation of the UKGS, namely in maintaining and improving dental and oral health of all students at school and to achieve optimal degree of the dental and oral health status of students.